2020
DOI: 10.1055/s-0040-1702229
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Protein Signatures of a Murine Venous Thrombosis Model and Slc44a2 Knockout Mice Using Quantitative-Targeted Proteomics

Abstract: The plasma compartment of the blood holds important information on the risk to develop cardiovascular diseases such as venous thrombosis (VT). Mass spectrometry-based targeted proteomics with internal standards quantifies proteins in multiplex allowing generation of signatures associated with a disease or a condition. Here, to demonstrate the method, we investigate the plasma protein signatures in mice following the onset of VT, which was induced by RNA interference targeting the natural anticoagulants antithr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Others have also shown that Slc44a2 increases thrombosis in various murine models 11 , 13 . Searching for mechanistic pathways through which Slc44a2 affects thrombosis, one study excluded an effect of Slc44a2 upon plasma proteins including coagulation factors, and proposed that Slc44a2 affects thrombosis through cellular pathways 12 . We confirm this prediction and extend this prior work, now demonstrating that Slc44a2 promotes thrombosis by regulating platelet metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have also shown that Slc44a2 increases thrombosis in various murine models 11 , 13 . Searching for mechanistic pathways through which Slc44a2 affects thrombosis, one study excluded an effect of Slc44a2 upon plasma proteins including coagulation factors, and proposed that Slc44a2 affects thrombosis through cellular pathways 12 . We confirm this prediction and extend this prior work, now demonstrating that Slc44a2 promotes thrombosis by regulating platelet metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS studies have associated the SLC44A2 locus with human phenotypes including: hearing loss, Meniere's disease, and venous thrombosis 3,9 . Recent studies have explored the role of SLC44A2 in thrombosis [10][11][12][13] . Two studies found that Slc44a2 promotes thrombosis in a mouse model of laser injury or venous stenosis but did not identify the mechanisms underlying this phenomenon 11,13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to elucidate the precise mechanisms that trigger clotting in venous thrombosis, Tilburg et al 56 characterized its plasma signature in a venous thrombosis murine knockout model using mass spectrometry-based proteomics, thereby establishing a new tool to diagnose such pathologies. 57 devices.…”
Section: Novel Diagnostic and Therapeutic Targetsmentioning
confidence: 99%
“…Indeed, quantitative MS has been successfully applied to understand the pathomechanisms of multiple diseases. 2 In this issue of Thrombosis and Haemostasis, Tilburg et al attempt to uncover the plasma protein signatures upon induction of VT using state-of-the-art MS-based targeted proteomics in combination with a murine knockout model for SLC44A2, a recently identified susceptibility locus for VT. 3,4 With this elegant approach, they not only gain information about changes in the plasma proteome in VT, but also demonstrate the great advantages of MS-based proteomics such as specificity and the possibility to expand a limited sample volume to a huge dataset.…”
mentioning
confidence: 99%